Cyclooxygenase COX-2a, a novel COX-2 mRNA variant, in platelets from patients after coronary artery bypass grafting - Censarek, Petra; Freidel, Kerstin; Udelhoven, Michael; Ku, Sun-Jung; Hohlfeld, Thomas; Meyer-Kirchrath, Jutta; Schrör, Karsten; Weber, Artur-Aron (Thrombosis and Haemostasis, 2004)
There are two principal cyclooxygenase isoforms referred to as COX-1 and COX-2. Recently, COX-3 has been identified. We have demonstrated the expression of COX-2 in platelets from patients after coronary artery bypass grafting (CABG). Careful biochemical analysis revealed that, when compared to recombinant COX-2, platelet COX-2 had a slightly higher electrophoretic mobility. Two COX-2 sequences (∼1.8 kb, ∼1.7 kb) were cloned from platelet mRNA. The ∼1.7 kb sequence, designated COX-2a, differed from the human COX-2 sequence only in a deletion from position +458 to +567. Similar to the human COX-3, there is a frame shift in the COX-2a sequence resulting in a TAA stop codon at position +490. Thus, the expression of a COX-2a protein corresponding to the 67 kDa COX-2 protein is not clear. However, the marked shifting from COX-2 to COX-2a in platelets from some patients after CABG is a striking finding.
Keywords: Cyclooxygenase-2; splice variant; platelets; coronary artery bypass grafting